Determination and validation of volume to be instilled for standardized intra‐abdominal pressure measurement in dogs. (15th July 2014) - Way, Leilani Ireland; Monnet, Eric
Abstract Objectives The objectives of this study were to determine (1) most appropriate volume of saline to be infused into the bladder prior to intra‐abdominal pressure (IAP) measurement, (2) to determine if a difference exists between IAP measurements before and after abdominal surgery, and (3) to assess the variability in IAP measurements associated with different saline volumes. Design Prospective study. Setting University teaching hospital. Animals Fifteen female research dogs, 7 undergoing ovariohysterectomy (OHE), and 8 undergoing laparoscopy. Interventions All dogs had urinary catheters placed and 4 consecutive IAP measurements measured using a different volume of instilled saline (0.25, 0.5, 1, and 2 mL/kg) at baseline. Measurements were repeated intraoperatively in laparoscopy dogs and postoperatively in OHE dogs. Measurements and main results For both groups of dogs, the volume infused into the bladder significantly affected IAP measurement. An instilled volume of 1 mL/kg of saline produced the best correlation (R2 = 0.44, P = 0.04) between IAP measurement and laparoscopic insufflator pressure. The mean (±SD) preoperative IAP (cmH2O) using 1 mL/kg instilled saline was 7.9 ± 1.4 and 9.6 ±1.9 for laparoscopy and OHE dogs, respectively. There was no difference in IAP before and after surgery in the dogs undergoing an OHE (P = 0.58). The volume of saline instilled into the bladder significantly affected the IAP (P = 0.0028). Conclusions One milliliter per kilogram instilled saline is recommended for standardized IAP pressure measurement in dogs. IAP in clinically normal dogs was not affected by abdominal surgery.